2011
DOI: 10.4293/108680811x13125733356477
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Virtual Reality Simulator Distinguishes Between Expert Gynecologic Laparoscopic Surgeons and Perinatologists

Abstract: Laparoscopic virtual reality simulators can measure relevant surgical skills and so distinguish between subjects having different skills level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A major factor driving an efficient learning curve is likely to be the reliance on correlation in duration of procedure and in performance of dexterity, which is a fundamental component of efficiency 10,31‐36 . Our findings clearly showed that the two methods of cavity preparation (virtual or physical) led to improvement in dexterity with similar beneficial impact on the learning curves.…”
Section: Discussionmentioning
confidence: 60%
“…A major factor driving an efficient learning curve is likely to be the reliance on correlation in duration of procedure and in performance of dexterity, which is a fundamental component of efficiency 10,31‐36 . Our findings clearly showed that the two methods of cavity preparation (virtual or physical) led to improvement in dexterity with similar beneficial impact on the learning curves.…”
Section: Discussionmentioning
confidence: 60%
“…Simple pelvic models have been used for training in pelvic examination and minor procedures such as endometrial biopsy, intra-uterine contraceptive device insertion, dilatation, and curettage. With the advent of gynaecological endoscopy, virtual reality system and haptic simulation model are introduced to facilitate this aspect of skills training [13][14][15] .…”
Section: Skill-based Simulation Trainingmentioning
confidence: 99%
“…Training with virtual reality system enables learning and practising surgical skills in a more real and pre-set critical rare situation with quicker setup 15 . The drawbacks are the lack of haptic sensation and depth perception, and prolonged training of >1 hour may cause fatigue of the eye and neck muscles and result in headache 13,14,39 . A combination of virtual reality system ultrasound simulation and mannequin ultrasound simulation is reported to reduce the time of scanning on real patient by 20% 40 .…”
Section: Effectiveness Of Simulation Trainingmentioning
confidence: 99%
“…Nonetheless, their practices become dominated by obstetrics, and their gynecologic surgical skills deteriorate. While cesarean sections are surgical in nature, the skill sets needed in these surgeries differ from the skills used in general gynecologic surgery …”
Section: Essaymentioning
confidence: 99%
“…While cesarean sections are surgical in nature, the skill sets needed in these surgeries differ from the skills used in general gynecologic surgery. 1 As gynecology has taken a back seat to obstetrics in our specialty, not only surgical skills but also diagnostic and management skills have deteriorated. This has led over the years to a culture in which endometriosis-a disease that affects an estimated one in ten women during their reproductive years-is rarely properly diagnosed and in which it seems acceptable and routine to perform surgery after many months away from the operating suite without informing patients.…”
mentioning
confidence: 99%